From Showing to Connecting. The Design of Exhibitions (Object Notes #1) (diségno, 2022)
The paper aims to focus within the history of exhibitions some experiences that are fundamental in describing the relationship between graphic design and exhibition practice. Through a selection of cases that have highlighted the qualities, disparities, and characterizing attributes of the exhibition system through design, the paper aims to read the project as a scenario of a production activity. The reading of some internal exhibitions in the 1980s and 1990s now become an opportunity to reflect on the relational system intrinsic to display practices. Starting from the reading and analysis of the editorial objects produced on the occasion of the exhibitions, the contribution attempts to show a relationship between the curator’s work, the graphic project carried out, the professional figures involved and the result obtained.The cases identified find in Germano Celant’s curatorial practice a focus on the graphic qualities of the exhibition activities he imagined. This practice makes it possible to emphasize within the paper the theme of exhibition design as an instrument of connec- tion. And, at the same time it emphasizes the disciplines involved in collective exhibitions to narrate the device-exhibition and the production qualities of the imagined systems.
Keywords: exhibitions; curating; display; graphic design; project